A qualitative study of online mental health information seeking behaviour by those with psychosis. Issue 1 (December 2016) - Aref-Adib, Golnar; O'Hanlon, Puffin; Fullarton, Kate; Morant, Nicola; Sommerlad, Andrew; Johnson, Sonia; Osborn, David
Abstract Background The Internet and mobile technology are changing the way people learn about and manage their illnesses. Little is known about online mental health information seeking behaviour by people with psychosis. This paper explores the nature, extent and consequences of online mental health information seeking behaviour by people with psychosis and investigates the acceptability of a mobile mental health application (app). Methods Semi-structured interviews were carried out with people with psychosis (n  = 22). Participants were purposively recruited through secondary care settings in London. The main topics discussed were participants' current and historical use of online mental health information and technology. Interviews were audio-recorded, transcribed and analysed by a team of researchers using thematic analysis. Results Mental health related Internet use was widespread. Eighteen people described searching the Internet to help them make sense of their psychotic experiences, and to read more information about their diagnosis, their prescribed psychiatric medication and its side-effects. Whilst some participants sought 'expert' online information from mental health clinicians and research journals, others described actively seeking first person perspectives. Eight participants used this information collaboratively with clinicians and spoke of the empowerment and independence the Internet offered them. However nine participants did not discuss their use of online mental health information with their clinicians for a number of reasons, including fear of undermining their clinician's authority. For some of these people concerns over what they had read led them to discontinue their antipsychotic medication without discussion with their mental health team. Conclusions People with psychosis use the Internet to acquire mental health related information. This can be a helpful source of supplementary information particularly for those who use it collaboratively with clinicians. When this information is not shared with their mental health team, it can affect patients' health care decisions. A partnership approach to online health-information seeking is needed, with mental health clinicians encouraging patients to discuss information they have found online as part of a shared decision-making process. Our research suggests that those with psychosis have active digital lives and that the introduction of a mental health app into services would potentially be well received.